An Innocent Esophageal Mucosal Bridge: Case Report and Literature Review - Tagore Sunkara MD; Eric Omar Then MD; Krishna Sowjanya Yarlagadda MD; Manan Jhaveri MD; Vinaya Gaduputi MD (SAGE Publishing, 2018)
An esophageal mucosal bridge is a rare finding that is seldom encountered on upper endoscopy. They most commonly present secondary to an underlying inflammatory disorder and cause chest pain and dysphagia, among other symptoms. More rarely, they present asymptomatically with no identifiable inflammatory conditions. Our case consists of a 31-year-old woman who presented with an asymptomatic, noninflammatory mucosal bridge of the esophagus. To our knowledge, this makes the third such case. The rarity of this condition coupled with the lack of epidemiologic data available make this case worthy for literature review.